Blended Learning LKPD Development Based On Learning Using Nearpod Applications For Integrated Learning In Elementary School - Yosi Fimala; Nur Azmi Alwi; Yalvema Miaz; Darmansyah Darmansyah (Journal of Innovation in Educational and Cultural Research, 2022)
This study aims to describe the validity, practicality, and an effectiveness of LKPD with the theme of growth and development of living things using the Blended Learning model in integrated thematic learning in grade III elementary school.This research is included in research and development (Research and Development) with the ADDIE model. Collecting data using observations, questionnaires, written tests and interviews and then analyzed quantitatively and qualitatively.This research produces a teaching material in the form of LKPD based on the Blended Learning model on the Theme of Growth and Development of Living Things, data analysis shows that the LKPD based on the Blended Learning model on the Theme of Growth and Development of living things is effective and interesting in learning.